Windthrow resistance of Norway spruce (Picea abies /L./ Karst.) forest cultures preliminary results - Đodan, Martina; Perić, Sanja, inženjerka šumarstva (2019)
Background and Purpose: Forest damage by wind is an important cause of economic loss in commercial forestry in the Republic of Croatia, as well as in many other European countries. Thus, windthrow resistance of trees represents a significant issue. Spruce forest cultures have shown the lowest resistance to windthrow so far. Nevertheless, there is not much insight into the relationship between trees and stand resistance to wind in the region. The objectives of this paper are to: (i) provide first evidence of the relation between tree characteristics prior to storm event in completely destroyed stands in comparison to slightly damaged stands, (ii) to evaluate the need to consider tree resistance to winds during thinnings, (iii) to evaluate if there is a need for windthrow stability assessment prior to replacement interventions. Materials and Methods: The paper investigates three individual cases of spruce forest cultures on three localities in the hilly part of Central Croatia in the fifth decade of age. Two of three stands were completely destroyed by the storm event during the year 2013. The experiment was established in the spring of 2010 using randomised block design with three replications. Based on total tree height (H) and diameter at breast height (DBH) the following parameters were calculated: wood volume (V), basal area (B) and slenderness coefficient. Descriptive statistics and correlation analyses were made in STATISTICA 8.2. Results: The results show overstocking, unfavourable structure and unfavourable slenderness coefficients (>80:1) in both cultures which were completely destroyed by wind. The correlation among variables revealed a significant relationship for all localities (p<0.05) when slenderness coefficient was compared with B and V (negative), but there was no correlation with H. Conclusions: Research supported the claim that slenderness coefficient and stand structural analysis can be good predictors of damages caused by wind.
Bibliografija: 70 jed.
Abstract.
Keywords: Šume -- Obična smreka -- Picea abies Karst. -- Vjetar -- Otpornost na vjetar -- Pošumljavanje